ChemInform Abstract: Green and Highly Selective Protocol for the Synthesis of Oximes. Issue 46 (24th October 2013) - Ghosh, Pranab; Subba, Raju
Abstract A green and efficient protocol for the selective synthesis of mono‐ or dioxime derivatives of various carbonyl compounds is developed.